Effects of the novel pyrimidynyloxybenzoic herbicide ZJ0273 on enzyme activities, microorganisms and its degradation in Chinese soils - Cai, Zhiqiang; Li, Shanshan; Zhang, Wenjie; Ma, Jiangtao; Wang, Jing; Cai, Jinyan; Yang, Guanghua (Environmental science and pollution research international, 2015)
Enzyme activity and microbial population in soils have important roles in keeping soil fertility. ZJ0273 is a novel pyrimidynyloxybenzoic-based herbicide, which was recently developed in China. The effect of ZJ0273 on soil enzyme activity and microbial population in two different soils was investigated in this study for the first time. The protease activity was significantly inhibited by ZJ0273 and this inhibiting effect gradually weakened after 60-day incubation. The results also showed that ZJ0273 had different stimulating effects on the activities of dehydrogenase, urease, and catalase. Dehydrogenase was consistently stimulated by all the applied concentrations of ZJ0273. The stimulating effect on urease weakened after 60-day incubation. Catalase activity was subject to variations during the period of the experiments. The results of microbial population showed that the number of bacteria and actinomycetes increased in ZJ0273-treated soil compared with the control after 20 days of incubation, while fungal number decreased after only 10 days of incubation in soils. DT50 (half-life value) and k (degradation rate constant) of ZJ0273 in S1 (marine-fluvigenic yellow loamy soil) and S2 (Huangshi soil) were found 69.31 and 49.50 days and 0.010 and 0.014 day −1 , respectively.